Brazilian version of the Cognitive Risk Profile for Pain Scale: translation, cross-cultural adaptation, and validation - Trabulsi, Lucianna Mirelle de Sá; Dibai Filho, Almir Vieira; Pontes-Silva, André; Costa de Jesus, Sulamizia Filomena; Mendes, Letícia Padilha; Araujo, Gabriel Gardhel Costa; Fidelis-de-Paula-Gomes, Cid André; Bassi-Dibai, Daniela; Rêgo, Adriana Sousa (São Paulo Medical Journal, 2026)
OBJECTIVES: To translate, cross-culturally adapt, and validate the Cognitive Risk Profile for Pain (CRPP) scale for Brazilians with chronic pain. Methods: We conducted a questionnaire-based validation study. Patients (males and females) with pain in any part of the body for > 3 months were included (n = 191). The participants were assessed using the CRPP scale, the Numeric Pain Rating Scale (NPRS), the Hospital Anxiety and Depression Scale (HADS), the Pain-Related Catastrophizing Thoughts Scale (PCTS), and the Brunel Mood Scale (BRUMS). After the translation, cross-cultural adaptation, and validation of the CRPP scale, we tested for ceiling or floor effects, construct validity, reliability, and internal consistency. Finally, the second application of the CRPP scale was used to measure test-retest reliability. RESULTS: Most participants were female, over 36 years of age, overweight, physically active, and had an average pain history of approximately 41 months. No ceiling or floor effects are observed. Nine domains of the CRPP scale correlated with the NPRS score, two domains of the HADS and PCTS, and six domains of the BRUMS. All CRPP domains demonstrated adequate reliability and internal consistency. CONCLUSION: The Brazilian version of the CRPP scale demonstrated adequate measurement properties in patients with chronic pain.